Magnetic resonance imaging for fistulography in perianal fistula: clinicoradiological correlation - Sarda, Hitesh; Pandey, Anshuman; Regmi, Sudip; Masood, Shakeel (International Surgery Journal, 2022)
Background: This article aims to review the role of magnetic resonance imaging (MRI) fistulography in evaluation of perianal fistula along with its concordance with clinical examination and impact on surgical intervention. Methods: A retrospective study of 61 patients who underwent surgery for anal fistula in RMLIMS collected from database from January 1, 2017 to September, 2021 Results: The study showed a significant MRI contribution to clinical evaluation in 65.6%. MRI provided significant information for complex fistulas than for simple fistulas (45% vs. 14.6%, p=0.01). Proportion of patients with significant MRI contribution increased with increasing Parks grade (grade 1, 8.3%; grade 2, 52.2%, p=0.001). The concordance between St. James Hospital grade and Parks classification was 0.768 (Kappa coefficient, p<0.00). Conclusions: Therefore, we propose inclusion of MRI in the preoperative surgical assessment of anal fistulas when recurrent, complex, high grade, or when the external opening is located more than 2 cm from the anal canal.